2018
DOI: 10.1016/j.jds.2018.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Bond strength of heat-pressed veneer ceramics to zirconia with various blasting conditions

Abstract: Background/purpose With the technology of dental prostheses and materials progress, the bond durability of the all-ceramic restoration system plays an important role in the oral environment. The purpose of this study was to evaluate the influence of the parameters of blasting on the shear bond strength between zirconia and pressed veneer ceramics. Materials and methods Zirconia was blasted with different alumina particle size subjected to two types of applied pressures.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 38 publications
1
14
1
Order By: Relevance
“…On the other hand, our results were in contrast to a previous study (36) which found that the bond strength of press-on veneered ceramic was significantly lower than layered one .This possibly clarified by the kinds and composition of the veneering materials in the two sub-groups were different. Also the higher ceramic pressing temperature that was used result in higher tetragonal to monoclinic transformation rate with concomitant higher coefficient of thermal expansion mismatch between the monoclinic zirconia and overlying veneer which in turn create higher tensile stresses at the interface.…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, our results were in contrast to a previous study (36) which found that the bond strength of press-on veneered ceramic was significantly lower than layered one .This possibly clarified by the kinds and composition of the veneering materials in the two sub-groups were different. Also the higher ceramic pressing temperature that was used result in higher tetragonal to monoclinic transformation rate with concomitant higher coefficient of thermal expansion mismatch between the monoclinic zirconia and overlying veneer which in turn create higher tensile stresses at the interface.…”
Section: Discussioncontrasting
confidence: 99%
“…For bonding with a resin cement, 3 lithium disilicate-reinforced glass ceramic specimens were acid-etched with 9.5% hydrofluoric acid gel (Bisco, IL, USA) for 30 s, washed with distilled water, dried, and silane primer (Espe TM Sil, 3M/ESPE, Seefeld, Germany) coated. The surfaces of 3 zirconia ceramic specimens were roughened using an air-borne particle abrasion technology with 50 µm alumina particles (Hi-aluminas, Shofu, Japan) under the pressure of 3 atm at a distance of 10 mm [23]. After placing the specimens in an electric furnace (Programat EP3000/G2), the temperature was raised to 1000 °C at a rate of 50 °C/min, held for 10 min, and then cooled to 25 °C in the furnace to restore the phase transformations occurred during the blasting procedure.…”
Section: Methodsmentioning
confidence: 99%
“…The high-strength zirconia (ZrO 2 ) has been applied to fixed prosthodontics because of its unique properties, such as high resistance to wear and distortion, chemical stability, thermal stability, and biocompatibility [1][2][3][4][5][6]. Although metalceramic (MC) dental crowns have been widely used due to good mechanical properties, zirconia coping or framework constructed with other dental ceramics to form porcelain-fused-to-zirconia (PFZ) prostheses is also developed to replace the traditional MC prostheses [2,3,7,8]. To achieve successfully long-term clinical practice veneering ceramics should be strongly bonded to the ZrO 2 core.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from liner application [11] and ceramic veneer type [12,13], the core-veneer bonding is apparently influenced by the surface properties of the ZrO 2 core [8,9,13,14]. For example, the increment in the surface area through sandblasting and mechanical grinding can enhance the mechanical interlocking between zirconia substrate and veneering ceramics to improve the bonding strength [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation